Institutional challenges for effective governance of consumptive wildlife tourism: case studies of marine angling tourism in Iceland and Norway - Solstrand, Maria-Victoria (Maritime Studies, 2015)
Published version, also available at http://dx.doi.org/10.1186/s40152-015-0021-1 A manuscript version of this article was part of Maria-Victoria Solstrand's doctoral thesis, which is available in Munin at http://hdl.handle.net/10037/7001 Good governance of consumptive wildlife tourism, a complex socio-ecological system, requires finding the right balance between natural resource and tourism management. Fishing takes the lead globally as the most popular product offering within consumptive wildlife tourism, and both Iceland and Norway offer a marine angling tourism product. The two countries offer similar pristine Arctic fjord topography and similar fish species; but the management strategies are very different. Iceland’s management strategy for marine angling tourism prioritizes ecosystem-based management of the fish as a living resource, and requires a full accounting of all statistics related to marine angling tourists’ activities. Norway’s strategy relies on estimates of key statistics such as total seasonal catch, and the regulations put the burden of accountability primarily on the tourists. Using data from a multiple case study analysis of marine angling tourism in Iceland and Norway, the differences in governance inter-dynamics are examined using a theoretical model developed to analyse a complex socio-ecological system as an institution. This paper analyses how the differing management strategies influence institutional function, conflict creation and mitigation. Special focus is placed on the impacts of non-compliance by the tourists. This study demonstrates how such a model can serve as a tool to perform an analysis of a socio-ecological system in order to better understand institutional inter-dynamics, thereby assisting in the creation of a more effective governance strategy.